Transformation Of Village Deliberative Body Supervision Policy In Gambut Mutiara Village Pelalawan Regency - Novita, Yosi; Zainal, Zainal; Ardiansyah, Ardiansyah (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2024)
The Village Consultative Body (BPD) is an institution needed to build and prosper the Village in its implementation. The Village Consultative Body (BPD) has the task and function to participate in building a transparent, accountable, and responsible village government, which results in a democratic and free village government. The Village Consultative Body (BPD) also functions as a channel for community aspirations to the village government, so that the village atmosphere becomes better. In carrying out supervision, the duties of the Village Consultative Body (BPD) are divided into three stages in carrying out its function as a supervisor of the performance of the village head. The first stage is planning village government activities, the second stage is implementing village government activities, and the third stage is reporting on the implementation of village government. By providing direction, supervision and input in building a better Village Government, the Village Consultative Body (BPD) is expected to make progress. The focus of this study is the problem of Supervision of the Village Consultative Body (BPD) on the Performance of the Village Head of Gambut Mutiara Village, Teluk Meranti District, Pelalawan Regency. This study was conducted by direct observation, namely observing directly in the field which was then followed by using interviews. The results of the study indicate that the implementation of village head performance supervision by the Village Consultative Body (BPD) has been quite good at the planning, supervision and reporting stages. This is evidenced by the success of the work program in 2023 to 2024 in Gambut Mutiara Village. In addition, village development allows the implementation of the main functions and tasks and village goals to be achieved.